Aprendizagem Colaborativa mediada pelo Squeak - Lima Filho, Cícero Bandeira (2013)
This research is focused on the area of digital technologies in education. Considering the various difficulties presented by the Brazilian education , particularly related to learning the sciences of nature , reveal national and international assessments is necessary to propose methodological strategies to counter the teaching model based on transmission / reception of content . This paper considers that the mere insertion of digital technologies in the classroom does not provide the expected benefits, which led to the adoption of strategies that would promote collaboration among participants. Held at a school in the municipality of Quixadá contemplated by the project One Laptop per student, aimed to analyze the contributions of an intervention that uses a methodology based on computer-supported collaborative learning. Was theoretically supported the following authors : Pozo (2009 ) , Mortimer (2000) , Driver (1999) and Cachapuz (2011) , dealing with the thematic science education , and Vygotsky (2007) , Damiani (2009 ), Colaco (2007),Coll (2010), Torres and Irala (2007) among others, that address themes related to collaborative learning . The methodological approach of the research was performed in two steps: initially a pilot and then the main stage, with participation of students of the 3rd year of high school. The research was qualitative approach, with the following categories of analysis: collaborative learning, study the contents of biology and learning mediated by Squeak. During the intervention the moments of peer interaction and socialization of the productions of the participants who took from the use of an application that enabled the creation of drawings and animations to represent some of the contents were analyzed Biology. It was noted during this study that the didactic situations created by the intervention increased interactions and that digital technologies offer benefits provided it is used in a collaborative perspective that supports and problematizes the study of curricular content.